Penerapan Green Economy Terhadap Peningkatan Sustainable Development Goals (SDGs) pada Industri Fashion Halal di Indonesia - Abib Noviyanto; Riza Arizona; Mardiyah Hayati (Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
Lifestyle and fashion have become an inseparable part of modern society. Excessive public consumption of apparel products causes clothing manufacturers to speed up their production performance. The production and consumption processes of society are primarily the cause of much of the natural damage caused. Where the waste from the fabric/textile dyeing production process from upstream to downstream is not managed properly, as is the disposal of worn-out apparel and is not managed responsibly. Economic globalization and the media industry are one of the factors that shape this condition. Lifestyle growth is a reference for society that is considered good or bad, up to the date or expiration. The purpose of this paper is to provide an introduction to the awareness of the fashion industry which is experiencing rapid progress, but many of the fashion industry movers and players ignore the current environmental problems. Provides an introduction to how fashion waste that is disposed of irresponsibly will cause environmental damage over time. The implications for producers, consumers and policy choices are to increase sustainable development goals with the aim of building an environmentally friendly fashion industry. This is followed by research illustrations regarding how to make bag products using the concept of sustainable fashion. A brief review of one of the fashion designers who pioneered the sustainable fashion/ ecofashion movement. This paper will also explain how sustainable fashion production and consumption is from an Islamic economic perspective.